1992
DOI: 10.1200/jco.1992.10.10.1635
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of etoposide pharmacokinetics and pharmacodynamics by cyclosporine in a phase I trial to modulate multidrug resistance.

Abstract: High-dose CsA produces significant increases in etoposide systemic exposure and leukopenia. These pharmacokinetic changes are consistent with inhibition by CsA of the multidrug transporter P-glycoprotein in normal tissues. Etoposide doses should be reduced by 50% when used with high-dose CsA in patients with normal renal and liver function. Alterations in the disposition of other multidrug resistance (MDR)-related drugs should be expected to occur with modulation of P-glycoprotein function in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
84
1
2

Year Published

1996
1996
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 276 publications
(88 citation statements)
references
References 29 publications
1
84
1
2
Order By: Relevance
“…Recently, oral dexverapamil has been found to increase the AUC of paclitaxel twofold (Berg et al, 1995), while it had no effect on the steady-state concentration of etoposide (Wilson et al, 1995a). With cyclosporin A and its analogue PSC 833, an increase in AUC and toxicity has been a consistent finding with any of the cytotoxic drugs tested so far (Lum et al, 1992;Bartlett et al, 1994;Boote et al, 1996). In contrast, the effects of other Reversal of epirubicin resistance in breast cancer 1161 chemosensitizers on the pharmacokinetics and -dynamics of cytotoxic drugs appear to depend on the particular agents used in combination.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Recently, oral dexverapamil has been found to increase the AUC of paclitaxel twofold (Berg et al, 1995), while it had no effect on the steady-state concentration of etoposide (Wilson et al, 1995a). With cyclosporin A and its analogue PSC 833, an increase in AUC and toxicity has been a consistent finding with any of the cytotoxic drugs tested so far (Lum et al, 1992;Bartlett et al, 1994;Boote et al, 1996). In contrast, the effects of other Reversal of epirubicin resistance in breast cancer 1161 chemosensitizers on the pharmacokinetics and -dynamics of cytotoxic drugs appear to depend on the particular agents used in combination.…”
Section: Discussionmentioning
confidence: 80%
“…In two randomized trials in metastatic breast cancer, quinidine and verapamil were not able to enhance epirubicin activity (Mross et al, 1993a;Wishart et al, 1994). Various studies have evaluated the effects of chemosensitizers on the pharmacokinetics and toxicity of cytotoxic agents (Kerr et al, 1986;Bisset et al, 1991;Lum et al, 1992;Philip et al, 1992;Mross et al, 1993b;Scheithauer et al, 1993;Bartlett et al, 1994;Berg et al, 1995;Motzer et al, 1995;Wilson et al, 1995a;Boote et al, 1996). The data from these studies have suggested that an increase in the area under the plasma concentration-time curve (AUC) and toxicity of cytotoxic drugs by chemosensitizers may be indicative of having achieved chemosensitizer concentrations that are high enough to effectively inhibit P-gp function (Fisher et al, 1996).…”
mentioning
confidence: 99%
“…Phase I studies showed that both CsA and PSC 833 increased the area under the curves of etoposide, daunorubicin and doxorubicin. [50][51][52][53][54] However, a disadvantage of this increase in plasma levels is that drug doses should be reduced to limit the toxic sideeffects. Side-effects have been reported at the clinically achievable concentrations of PSC 833, CsA and Vp used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…14 Samples with more than 70% of leukemic cells in the control wells after 4 days of culture (without drug) and a control OD value higher than 0.050 arbitrary units (adjusted for blank values) were used to calculate the LC 50 value, ie the concentration of drug that is lethal to 50% of the cells (in g/ml). 13,16 The LC 50 of DNR in the presence of the modulator was corrected for the cell kill mediated by the modulator itself. The modulating effect on DNR cytotoxicity was expressed as the ratio between the LC 50 value of DNR with and without modulator: a ratio Ͼ1 indicates a sensitizing effect of the modulator, ie the LC 50 of single DNR was higher than the LC 50 of DNR in the presence of the modulator; a ratio Ͻ−1 indicates an adverse effect of the modulator, ie the LC 50 of DNR in the presence of the modulator is higher than the LC 50 of single DNR.…”
Section: In Vitro Drug Resistance Assaymentioning
confidence: 99%
See 1 more Smart Citation